Short term effectiveness of Structured Exercise Therapy Protocol on Cardio-respiratory parameters in subjects with COVID - Chintamani, Radhika; Burungale, Mayuri (International Journal of Psychosocial Rehabilitation, 2020)
Introduction: It is already proven that COVID subjects are known to have symptoms like breathlessness at rest, fever, sore throat, and other pneumonia-like symptoms. Few studies have demonstrated physiotherapy intentionally enhances invulnerability towards infection by different exercises on the stipulated part, thus increasing the strength of that part. Cardiopulmonary rehabilitation is known to be useful in treating subjects with cardiorespiratory symptoms. Few studies have already demonstrated exercises have a strong significant effect on managing subjects with COVID on high-flow nasal cannulas as well as mechanical ventilation. According to the authors’ knowledge, there are very few studies demonstrating the effectiveness of the Structured Exercise Therapy Protocol for COVID subjects in both types of oxygen therapy; hence, this study is being undertaken. Objective: To investigate the short-term effectiveness of structured exercise therapy protocol in subjects diagnosed with COVID on high-flow nasal cannula versus structured exercise therapy protocol on mechanical ventilation. Methodology: This is a randomized clinical trial conducted on 124 subjects. Subjects were randomly divided into two groups: Group A, 62 subjects with high-flow nasal cannulas who were given a structured exercise therapy protocol, and Group B, 62 subjects with mechanical ventilation who were given a structured exercise therapy protocol. Results: Both the groups showed significant improvement with respect to the structured exercise therapy protocol. On comparison Group A showed high significant results in improvement in modified Borg’s scale of dyspnea, SP02, Respiratory rate, X-ray changes, heart rate, COVID and number of active cough extractions demonstrated significant changes with p-values of <0.001, <0.05, <0.05, and <0.001, respectively. Whereas Group B showed significant improvement with a p-value < 0.05 for all the parameters. Conclusion: The treatment showed significant improvement in all the outcome measures in group A, which is subjects with high-flow nasal cannulas. Hence, the conclusion is that the structured exercise physiotherapy protocol in subjects with high-flow nasal cannula showed early and more significant improvement in subjects with COVID in all the respiratory parameters against subjects with mechanical ventilation.